Living with Transgenic Animals - Clark, Jonathan L. (Humanimalia, 2014)
This article examines Farm Sanctuary’s failed effort to save the Enviropigs. In the Spring of 2012, after losing the main source of funding for its Enviropig project, the University of Guelph, in Ontario, Canada, killed the last sixteen members of this line of transgenic pigs, despite Farm Sanctuary’s offer to place them in permanent homes. The university claimed that transferring the pigs to a sanctuary would have violated laws and policies governing the disposition of transgenic laboratory animals. Through a detailed account of this case, this paper reflects on what it means to create a subcategory of laboratory animals who are categorically ineligible for life after the laboratory.